SURVEY OF PATIENTS’ PERCEPTION OF HOSPITAL FOOD SERVICES AT AFIC – NIHD RAWALPINDI - Zahid, Maryam; Zaidi, Sabeen Khurshid; Naqvi, Shahab; Iqbal, Sana; Maqsood, Bilal; Iqbal, Afsheen (Pakistan Armed Forces Medical Journal, 2015)
Objective: To determine the satisfaction level of patients towards the food quality.Study Design: Descriptive cross-sectional study.Place and Duration of Study: This study was carried out at Armed Forces Institute of Cardiology in Rawalpindi Pakistan from 3rd Nov 2014 – 30th Jan 2015.Material and Methods: A pretested questionnaire was used to determine the patients’ satisfaction level and perception towards food quality at a 250 bedded tertiary cardiac care hospital. Patients were selected through non probability convenience sampling. Demographic data was also collected for all patients. Data was entered and analyzed in IBM SPSS Statistics 21 (statistical package for social sciences).Results: Question responses were coded on a scale of 1-5, representing the Likert Scale on the survey (Excellent=5, Good=4, Satisfactory=3, ordinary=2, Unacceptable=1). The Cronbach alpha coefficient for the 13 questions was .86 (>0.7), suggesting that the items have relatively high internal consistency. The overall rating for food quality was fairly high i.e. 4.4. The rating of food’s temperature that is hot food’s temperature was 3.7 and cold food temperature was 3.9.Conclusion: The results show that patients’ perception towards overall food service system was above average whereas improvement should be made in maintaining food temperatures. Patients’ suggestions regarding the betterment of foodservice will be helpful in making decisions for continual improvement of hospital food services.